Impact of age on cardiovascular drug use in patients with chronic kidney disease - Villain, Cédric (Clin Kidney J, 2019)
BACKGROUND: Elderly patients with chronic kidney disease (CKD) are often excluded from clinical trials; this may affect their use of essential drugs for cardiovascular complications. We sought to assess the impact of age on cardiovascular drug use in elderly patients with CKD. METHODS: We used baseline data from the Chronic Kidney Disease-Renal Epidemiology and Information Network (CKD-REIN) cohort including 3033 adult patients with CKD Stages 3 and 4. We studied the use of recommended drugs for coronary artery disease (CAD), stroke and atrial fibrillation by age, after adjusting for socio-demographic and clinical conditions. RESULTS: The patients’ mean age was 66.8 years (mean estimated glomerular filtration rate 32.9 mL/min/1.73 m(2)). The prevalence of CAD was 24.5% [81.3% receiving antiplatelet agents, 75.6% renin–angiotensin system (RAS) blockers, 65.4% β-blockers and 81.3% lipid-lowering therapy], that of stroke 10.0% (88.8% receiving antithrombotic drugs) and that of atrial fibrillation 11.1% (69.5% receiving oral anticoagulants). Compared with patients aged <65 years, older age (≥65 years) was associated with greater use of antithrombotic drugs in stroke [adjusted odds ratio (aOR) (95% confidence interval) = 2.83 (1.04–7.73) for patients aged (75–84 years)] and less use of RAS blockers [aOR = 0.39 (0.16–0.89) for patients aged ≥85 years], β-blockers [aOR = 0.31 (0.19–0.53) for patients aged 75–84 years] and lipid-lowering therapy [aOR = 0.39 (0.15–1.02) for patients aged ≥85 years, P for trend = 0.01] in CAD. Older age was not associated with less use of antiplatelet agents in CAD or oral anticoagulants in atrial fibrillation. CONCLUSIONS: In patients with CKD, older age per se was not associated with the underuse of antithrombotic drugs but was for other major drugs, with a potential impact on cardiovascular outcomes.